(untitled) (Research, Society and Development, 2021)
Reproductive traits relatively have low or medium heritability and do not exhibit a remarkable response to phenotypic selection. Therefore, the inclusion of genetic information from genes associated with reproductive capacity can efficiently improve the selection response. The main important genes affecting prolificacy and their genetic diversity in different breeds of sheep have been studied on a global scale. Where, different mutations associated with reproductive traits, including ovulation rate and litter size, have been found in various sheep breeds around the world. An overview of studies on major proliferation genes showed that some alleles may express different phenotypic effects in different breeds and therefore, further studies on interaction effects are needed for a greater understanding of the genetic control of reproduction in sheep. Regarding the evaluation methodology for prolificacy traits, the application of new technologies is necessary to find new variants, which is essential for future studies. The methodology adopted was a descriptive study, resulting in a literature review based on worldwide scientific articles.